C.G. Bartholomew – H.A. Thomas, "The Minor Prophets. A Theological Introduction" (A Theological Introduction series; Downers Grove, IL: Inter-Varsity Press 2023) - Szmajdziński, Mariusz (The Biblical Annals, 2025)
Book review: C.G. Bartholomew – H.A. Thomas, "The Minor Prophets. A Theological Introduction" (A Theological Introduction series; Downers Grove, IL: Inter-Varsity Press 2023). Pp 390. € 52. ISBN: 978-1-5140-0168-4.